The Development of Virtual Laboratory Learning Media for The Physical Optics Subject - Billah, Arif; Widiyatmoko, Arif (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
This study aims to produce virtual laboratory interactive learning media that is effective and practical for the subject of physical optics. It uses the Research and Development (R & D) method. The material in the learning media includes dispersion, diffraction, interference, and polarization. Users of this product can be directly involved in observing, measuring and taking practical data. Product development has been validated by material expert, media expert, and practitioners (teachers). This product has also been tested in one-to-one, small groups, and field trial. Based on the results of the assessment by material expert, media expert, teachers, and field trial, this learning media software is categorized as “excellent” with a value of 4.63 for validity, “medium” with an n-gain value of 0.37 for effectiveness, and “excellent” with a value of 4.49 for practicality